Factors Influencing Investor Responses to Earnings Related Announcements in The Pandemic Era of Covid-19 - Yohanes Mardinata Rusli; Kandi Sofia Senastri Dahlan; Eka Dian Rani; David Harianto (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aims to examine the Effect of Growth Opportunities on Earning Related Announcements. The effect of Debt Policy on ERC (Earnings Response Coefficient) and the effect of Company Size on ERC (Earnings Response Coefficient) is the role of the company's reputation as a moderator between the Effect of Growth Opportunities on Profit-Related Announcements. there is a role for the company's reputation as a moderator between the effect of debt policy on the ERC (Earnings Response Coefficient) and the role of the company's reputation as a moderator between the effect of company size on the ERC (Earnings Response Coefficient). by using multiple regression analysis. The researcher concludes that there is an influence of growth opportunities and corporate size on the earnings response coefficient. but the debt policy has no effect on the earnings response coefficient. then there is the role of corporate reputation as a moderator of the influence of growth opportunities and corporate size on earnings response coefficient but there is no role of corporate reputation as a moderation of the effect of debt policy on earnings response coefficient.